Management of relapsed or refractory large B-cell lymphoma in patients ineligible for CAR-T cell therapy. Issue 3 (4th March 2022) - Perrone, Salvatore; Lopedote, Paolo; Levis, Mario; Di Rocco, Alice; Smith, Stephen Douglas
ABSTRACT: Introduction: Chimeric antigen receptor T (CAR-T) therapy has revolutionized the treatment of relapsed/refractory large B-cell lymphoma (LBCL). However, patients who are excluded or have no access to CAR-T represent a challenge for clinicians and have generally a dismal outcome. The landscape for this category of patients is constantly evolving: new agents have been approved in the last 2–3 years, alone or in combination, and novel treatment modalities are under investigation. Areas Covered: Thereafter, we reviewed the currently available therapeutic strategies: conventional chemotherapy, antibody–drug conjugate ADC (mainly polatuzumab and loncastuxumab), bispecific antibodies (CD19/CD3 and focus on novel CD20/CD3 Abs), immunomodulatory drugs (covering tafasitamab and lenalidomide, checkpoint inhibitors mainly in PMBL), small molecules (selinexor, BTK, and PI3K inhibitors), and the role of radiotherapy. Expert Opinion: Navigating this scenario will uncover new challenges, including identifying an ideal sequence for these therapies, the most effective combinations, and search for consistent predictive factors to help selecting the appropriate population of LBCL patients. At present, supporting clinical research for CAR-T ineligible patients, a new and challenging group, must remain a major focus that is complementary to advances in CAR T-cell therapy.